Sintesis membran Poliuretan dari Karagenan dan 2, 4 Toylulene diisosianat - Marlina, Marlina (Jurnal Rekayasa Kimia & Lingkungan, 2010)
This research studied the synthesis of Polyurethane (PU) Membrane from Carrageenan and 2,4 toylulene diisocyanante (TDI). The PU membrane made from the Gracilaria sp of red seaweed has rendement of 60.5% from the total weight of the dried sea grass. The produced Carrageenan has pure properties with containing many OH groups which can be used to synthesize membrane. The dope solution to produce good membrane was made at the temperature of 60 oC for the reaction of 5 minutes by varying concentration of carrageenan 5-35 % (b/v). PU membrane was constructed using petri dish with the thickness of about 0.1 mm. To control the thickness of the membrane, the volume of dope solution was used about 12 mL, and the membrane was produced with 10 cm in diameter. The membrane had been synthesized at the temperature of 60 oC with varied concentration of Carrageenan 15% (b/v) to the toylulene diisocyanate (TDI). The produced membrane has the optimal properties with the tensile strength of 340 kgf/mm2, the elongation percentage of 9%, the glass temperature transition of 243.6 oC and the melting point of 423.02 oC. The optimum PU membrane obtained was good in mechanical and physical properties, strong, elastic and transparent.Keywords: carrageenan, flux, membrane, polyurethane, rejection factor, TDI